2014
DOI: 10.1149/06117.0015ecst
|View full text |Cite
|
Sign up to set email alerts
|

A Cahn-Hilliard Modeling of Metal Oxide Thin Films for Advanced CMP Applications

Abstract: Chemical mechanical planarization (CMP) process enables topographic selectivity through formation of a protective oxide thin film on the recessed locations of the deposited metal layer, while a continuous chemical oxidation reaction is followed by mechanical abrasion takes place on the protruding locations. This paper demonstrates a new approach to CMP process optimization in terms of analyzing the nano-scale surface topography of the protective metal oxide films and modeling their growth through a Cahn-Hillia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This can be attributed to the variability in the corrosion and passivation behavior of the WO 3 aligning with our earlier studies. 20 Titanium MRR values, on the other hand, showed an increase with the increasing H 2 O 2 in the formulated slurries. This can be explained by the faster rate of passive film formation for Ti as represented in Figure 5.…”
Section: Electrochemical Evaluations On W/timentioning
confidence: 83%
See 2 more Smart Citations
“…This can be attributed to the variability in the corrosion and passivation behavior of the WO 3 aligning with our earlier studies. 20 Titanium MRR values, on the other hand, showed an increase with the increasing H 2 O 2 in the formulated slurries. This can be explained by the faster rate of passive film formation for Ti as represented in Figure 5.…”
Section: Electrochemical Evaluations On W/timentioning
confidence: 83%
“…Based on our earlier studies, we have demonstrated that the oxidation of W is driven by the nucleation and growth mechanisms controlled by the Oswald ripening on the surface. 20 Furthermore, the surface oxide structures and the roughness correlate to the CMP removal rate and defectivity performance. 17 The passive film formation was confirmed by the X-Ray Reflectivity measurements and the Pilling-Bedworth ratio calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the metallic films tend to form a metal oxide layer, which is known to be a protective oxide film for the W CMP [5]. The oxidation reaction on the metal surface results in the metal oxide film formation through nucleation and growth for which the Oswald ripening (reverse diffusion) moderates the film formation [2]. We have demonstrated in earlier work that this mechanism results in the formation of oxide peaks that tend to change the surface roughness as a function of the oxidizer concentration [3].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a new modeling approach was introduced to CMP process optimization by means of topographic evaluation of the metal oxide thin films. Cahn Hilliard Equation (CHE) was utilized as an alternative to classical nucleation theory in terms of analyzing the topographic nature of the protective metal oxide nano films and modeling their growth, which was observed to affect the CMP performance [2]. It was concluded that the material removal rate mechanisms and the consequent planarization performance depend on the nature of nucleation of the metal oxide films, which is tailored by the oxidizer concentration.…”
Section: Introductionmentioning
confidence: 99%